Catch me if you can: Detecting the effect of stock manipulation to Asian markets - Anion, Elmer G. (Animo Repository, 2017)
The stock market has proven to be a great financial platform not only for corporate financing but as a financial investment to the public as well. The problem, however is if returns are acquired through illegal means such as stock manipulation. With numerous cases of stock market manipulation arising around the world, particularly the Asian markets, it can negatively affect the market and the economy. With that said , this paper aimed to delve into the irregularities of such excessive returns by employing the general autoagressive conditional heteroskedascity (GARCH) model to detect if there is a possibility to spot stock market manipulation and event study methodology (ESM) to determine the effect of the news of the company under investigation for such act to the stock price. The results proved that stock market manipulation exists and it is an issue that needs to be addressed. Both methodologies proved their functionality and effectiveness by being able to generate a threshold to spot that would warn investors to be on the lookout and the other to discern the impact of the news of stock manipulation to the market.